Optical coherence tomography in the evaluation of structural changes in primary open-angle glaucoma with and without elevated intraocular pressure - Trenkić Božinović, Marija Srbobran; Zlatanović, Gordana; Jovanović, Predrag; Veselinović, Dragan; Đorđević Jocić, Jasmina; Radenković, Marija; Resan, Mirko (Vojnosanitetski pregled, 2016)
Background/Aim. Glaucoma is a progressive optic neuropathy characterized by damage of the retinal ganglion cells and their axons and glial cells. The aim of this study was to evaluate the differences and connections between changes in the visual field and the thickness of the peripapillary retinal nerve fiber layer (RNFL), using optical coherence tomography (OCT) in patients with primary open-angle glaucoma with normal and elevated intraocular pressure (IOP). Methods. This prospective study included 38 patients (38 eyes) with primary open-angle glaucoma with normal intraocular pressure (NTG) and 50 patients (50 eyes) with primary open-angle glaucoma with elevated intraocular pressure (HTG), paired by the same degree of structural glaucomatous changes in the optic nerve head and by age. OCT protocols ’fast RNFL thickness’ and ’fast optic disc’ were used for testing. The patients’ age, gender, best corrected visual acuity (BCVA), IOP, stereometric and functional parameters were compared. Results. The average age of the examined population was 65.49 ± 9.36 (range 44–83) years. There was no statistically significant difference by age and by gender between the two study groups (p = 0.795 and p = 0.807, respectively). BCVA was higher in patients with NTG but there was no statistically significant difference compared to HTG patients (p = 0.160). IOP was statistically significantly higher in patients with HTG compared to NTG patients (17.40 ± 2.77 mmHg vs 14.95 ± 3.01 mmHg, p = 0.009). The cup/disc (C/D) (p = 0.258), mean deviation (MD) (p = 0.477), corrected patern standard deviation (CPSD) (p = 0.943), disk area (p = 0.515), rim area (p = 0.294), rim volume (p = 0.118), C/D area R (p = 0.103), RNFL Average (p = 0.632), RNFL Superior (p = 0.283) and RNFL Inferior (p = 0.488) were not statistically significantly different between the groups. Conclusion. OCT measurements of the RNFL thickness provide clinically significant information in monitoring of glaucomatous changes. There are no differences in the patterns of RNFL defects per sectors and quadrants between NTG and HTG, measured by OCT.